Chromium adsorption using powdered leaves of Prosopis cineraria: Kinetic, isotherm, and optimization by response surface methodology - Maedeh Soleimani; Hamzeh Ali Jamali; Milad Mousazadehgavan; Reza Ghanbari (Desalination and Water Treatment)
In this study, the effectiveness of Prosopis cineraria leaves powder in removing chromium from an aqueous solution was examined. The test was done in batch mode and the effect of Prosopis cineraria doses (1–5 g/L), initial pH (1.5–3.5), initial concentrations of chromium (10–50 mg/L), and contact times (15–75 min) on the biosorptioon process was examined. The results of response surface methodology indicated that under the best operating conditions with Prosopis cineraria dose of 3.98 g/L, initial chromium concentration of 25.41 mg/L, contact time of 59.82 min and pH of 2.02, chromium removal efficiency was selected as a maximum value of 89.65%. The adsorption aligns with the Langmuir isotherm and pseudo-first-order kinetic models. The maximum adsorption capacity for chromium was determined to be 55.55 mg/g, indicating the high efficacy of Prosopis cineraria in removing chromium ions. The findings suggest that Prosopis cineraria leaves powder could be a cost effective alternative to more expensive heavy metal adsorbents from aqueous solution, but notes more research is needed on the efficiency of Prosopis cineraria for industrial wastewater. Future studies should focus on SEM, XRD and FTIR analysis to enhance understanding of the adsorption mechanisms and potential applications for chromium removal.